Electromagnetic properties of lanthanum iron garnet filled PVDF-polymer composite at microwave frequencies using finite element method (FEM) and Nicholson–Ross–Weir (NRW) method - Soleimani, Hassan; Yahya, Noorhana; Sabet, Maziyar; Abbas, Zulkifly; Soleimani, Hojjatollah; Kozlowski, Gregory; Ghotbi, Mohammad Yeganeh (Forum of Chalcogeniders, 2014)
In our previous work, the lanthanum iron garnet-filled PVDF-polymer nanocomposite has been prepared. The real and imaginary parts of relative permittivity and permeability of mentioned sample were obtained simultaneously using the Nicholson-Ross-Weir (NRW) method based on the measurement of the reflection and transmission coefficients of the materials. In this study, the electric field distribution and attenuation at rectangular waveguide loaded sample were investigated based on the Finite Element Method (FEM). The computations of the reflection and transmission coefficients (S-parameters) were implemented using both the FEM and NRW methods. The results were compared with the measured reflection and transmission coefficients using the rectangular waveguide in conjunction with an Agilent N5230A PNA-L Vector network analyzer (VNA) at X-band frequencies (8 GHz- 12 GHz). The results of the relative error indicated that, among the two applied methods, the FEM is more accurate than the NRW method.